Expression pattern of inflammatory response genes and their regulatory micrornas in bovine oviductal cells in response to lipopolysaccharide: implication for early embryonic development. - Sally Ibrahim; Dessie Salilew-Wondim; Franca Rings; Michael Hoelker; Christiane Neuhoff; Ernst Tholen; Christian Looft; Karl Schellander; Dawit Tesfaye (PLoS ONE, 2015)
In the present study, we used an in vitro model to investigate the response of the oviduct with respect to inflammatory mediators and their regulatory microRNAs in case of bacterial infection and subsequent association with embryo survival. For this, we conducted two experiments. In the first experiment, cultured primary bovine oviductal cells (BOEC) were challenged with lipopolysaccharide (LPS) for 24h and the temporal expression pattern of inflammatory mediators and their regulatory microRNAs were measured at 0, 3, 6, 12, 24 and 48h after LPS treatment. Intriguingly, the temporal patterns of all miRNAs except miR-21 were significantly up-regulated at 6h after LPS treatment. Whereas, we observed significant overexpression of pro-inflammatory mediators as tumor necrosis factor alpha (TNFα) and interleukin-1 beta (IL1β) after LPS challenge for 24h. On the other hand, the expression level of essential elements like oviductal glycoprotein 1 (OVGP1) and insulin-like growth factor 2 (IGF2) was significantly decreased in challenged groups compared with control. Moreover, miR-155, miR-146a, miR-223, miR-21, miR-16 and miR-215 have shown a clear suppression in challenged group after LPS treatment. In the 2nd experiment there were four groups of blastocysts produced, namely embryo+LPS free media, embryo+LPS, BOEC+embryo and BOEC+embryo+LPS. The suboptimal oviduct environment due to LPS challenge is found to have a significant influence on the expression of inflammatory response genes (TNFα and CSF1), stress response genes (SOD and CAT), mitochondrial activity, reactive oxygen species (ROS) accumulation and apoptotic level either in cultured or co-cultured blastocysts. Collectively, LPS challenge led to aberrant changes in oviductal transcriptome profile, which could lead to a suboptimal environment for embryo development.